Beta-Catenin in Pseudoexfoliation Syndrome - Joanna Stafiej; Marta Hałas-Wiśniewska; Magdalena Izdebska; Maciej Gagat; Alina Grzanka; Grażyna Malukiewicz (Applied Sciences, 2020)
To find whether it is possible that beta-catenin, associated with the development of serious systemic diseases, as well as the neoplastic process, plays a role in the development of pseudoexfoliation syndrome (PEX). If so, identifying PEX, an age-related, vision-threatening disorder of elastic fibers, which is manifested in eyes by the accumulation of an abnormal fibrillar material on the tissues of the anterior segment, with its poorly understood pathogenesis, may be an early indicator of other systemic diseases. The specimens of anterior lens capsules were obtained during routine cataract surgeries from patients with PEX (study group) and those without it (control group). Patients with previously diagnosed renal, cardiac or neoplasm diseases were excluded. In order to determine the localization of β-catenin at the ultrastructural level, the post-embedding colloidal gold (AU) method was used. For the analysis of the presence of proteins involved in cell–cell junctions, including β-catenin, fluorescence staining was performed. An enhanced accumulation of AU in the area of cell junctions in the PEX group was observed in comparison to control patients. A statistically significant increase in the level of β-catenin expression in lens epithelial cells (LECs) for the PEX group (MFI = 808.98) in comparison to the control patients (MFI = 731.6) was also noted. Our study presented the increase in the β-catenin in LECs of PEX group in comparison to control patients. It might be possible for PEX, due to it being easily recognizable, to be the first indicator of serious kidney or cardiac diseases, as well as cancer metastases. Further studies are needed in order to confirm this hypothesis.